Bioanalytical method for the simultaneous estimation of atoltivimab, maftivimab and odesivimab in rat plasma by LCMS/MS and its application to a pharmacokinetic study - Syed, Ibrahim Baje; Nannapaneni, Madhavi (Creative Pharma Assent, 2024)
Background: A quick, accurate, reproducible, and straightforward liquid chromatography-tandem mass spectrometry(LC-MS/MS) system employing Atoltavimab, Maftivimab, and Odesivimab as an internal standard for Zanamivir quantification was achieved. Zanamivir is a neuraminidase inhibitor that effectively treats influenza caused by influenza A and B viruses. Methodology: Whenever we use the Kinetex C-18 column, all HPLC parameters and conditions are obeyed, so we use this column. Separation was performed on a Kinetex C18 column (100 mm x 4.6 mm, 2.6µm) using isocratic elution with a buffer containing 1mL of formic acid in 1Lit of water and a mobile step consisting of a 40:60 v/v mixture of two elements, buffer and acetonitrile, with a flow rate of 1mL/min at 300C temperature was used. Results & Discussion: We used different stationary phases in the optimization process, such as C18, C8, and CN-propyl. Using a kinetex C18 column with dimensions of (100 mm x 4.6 mm, 2.6 µm) connected to a PDA detector, we obtain strong peak shapes of Atoltivimab, Maftivimab, and Odesivimab from various trials. Flow rates in the mobile process were set to 1 mL/min. Conclusion: Atoltivimab, Maftivimab, and Odesivimab analysis was completed in 7 minutes over a good linear concentration range of 5ng/mL to 100ng/mL (r2 = 0.999), 5ng/mL to 100ng/mL (r2 = 0.999), and 5ng/mL to 100ng/mL (r2 = 0.9998). The findings of the precision and recovery studies are within the appropriate range.